Front Cover: Improvements in Metabolic Syndrome by Xanthohumol Derivatives Are Linked to Altered Gut Microbiota and Bile Acid Metabolism. Issue 1 (2nd January 2020) - Zhang, Yang; Bobe, Gerd; Revel, Johana S.; Rodrigues, Richard R.; Sharpton, Thomas J.; Fantacone, Mary L.; Raslan, Kareem; Miranda, Cristobal L.; Lowry, Malcolm B.; Blakemore, Paul R.; Morgun, Andrey; Shulzhenko, Natalia; et al.
Abstract : Mol. Nutr. Food Res . 2020, 64, 1900789 DOI: 10.1002/mnfr.201900789 Hops‐derived xanthohumol (XN) and derivatives DXN and TXN reduce high‐fat diet (HFD)‐induced obesity and metabolic disorders in rodents. In article number 1900789, Adrian F. Gombart and co‐workers show that these compounds function as novel modulators of gut microbiota, reducing diversity and altering bile acid metabolism to ameliorate HFD‐induced obesity, adipose inflammation, and metabolic syndrome.